Fruit rot causing by Athelia rolfsii (Sclerotium rolfsii) on jackfruit (Artocarpus heterophyllus) in China - Yi, Run Hua (Plant disease, 2023)
Artocarpus heterophyllus, known as jackfruit, was a tropical fruit and cultivated extensively as nutritional and medicinal properties in southern China in recent year. During July 2022, fruit rot was observed on the fruits at the bottom of jackfruit trees in an orchard in Zhanjiang, Guangdong (N21°9' 27" E110°17' 54") 3-4 days after typhoon. The incidence rate of fruit was about 0.3%. The initial symptom was white mycelia appearing on the surface of fruits. Mycelia with rhizomorphs spread rapidly over the fruits, formed white, often fan-shaped mats with the rapeseed size sclerotia. The infected fruits were water-soaked, quickly became rotten, and fell off. Sclerotia from disease fruits were incubated on PDA with 50 mg/L ampicillin at 25-28℃ in the dark for 2 days. Hyphae tips were transferred to get the purified isolates. Colonies with a radial growth rate of 23.2 mm/day had abundant aerial mycelia and profuse sclerotia on PDA. Hyphae of the isolates were transparent, branched, with clamp connections at septa, usually 2.9-8.3 µm (Ave. 5.8 µm) (n>30) wide. Aerial mycelia were whitish-cottony, with many narrow rhizomorphs. Spherical sclerotia developed at about 10 days after incubation, and gradually changed from white to tan-to-dark brown, and mature sclerotia were about 1.7 mm in size. The morphological characteristics was similar to those of Sclerotium rolfsii (teleomorph: Athelia rolfsii). To accurately identify the fungus, the internal transcribed spacer gene (ITS) and large subunit rRNA gene (LSU) of isolate CASS-BLM-1 were PCR amplified with primer pairs ITS1/ITS4 (White et al 1990) and V9G/LR5 (Klaubauf et al 2014). The amplicons were sequenced and deposited in GenBank with accession number OP535473 (ITS) and OP535474 (LSU). BLASTn results showed that the nucleotide sequences of ITS and LSU had high identity with corresponding sequences of A. rolfsii isolates CBS 191.62 (ITS: MH858139, 472/474(99.58%); LSU: MH869724, 882/885(99.66%)) (Vu et al 2019). Phylogenetic analysis based on ITS sequence data was obtained according to maximum likelihood method using MEGA analysis software, CASS-BLM1 was grouped in A. rolfsii clade with 100% bootstrap support value. Based on morphology and DNA sequences, the fungus was identified as A. rolfsii (anamorph: S. rolfsii). To fulfil Koch's postulates, healthy fruits on the tree and detached fruits were inoculated with 7-day-old sclerotia of isolate CASS-BLM1. Five unwound sites and five wound sites with a sterile needle were tested on each fruit and a sclerotium was put at each site. Fruits not inoculated with sclerotia were used as control the test was repeated three times. All fruit were enclosed in transparent plastic bags with sterile absorbent cotton moistened with sterile distilled water. The indoor and outdoor temperatures ranged from 25 to 30 ℃. Three days later, white mycelia were observed on all inoculation sites, and 5 days later, the inoculated fruits began to rot, while control fruits remained healthy. The same fungus with identical morphology and DNA sequences was re-isolated from the inoculated sites. Previously, A. rolfsii was reported to cause fruit rot disease on jackfruit in Bangladesh (Elahi et al 2021), this is the first report of A. rolfsii causing fruit rot on jackfruit in China. A. rolfsii is suitable for high temperature and humidity environment (Punja 1985), this report will help farmers to diagnose this disease, especially to strengthen the disease prevention during the typhoon season